Examining molecular biology in humans. (April 2009) - Parker, Alex; McCaffery, Ian; Patterson, Scott D.
Significant advances in biological knowledge have been made through the application of genomic, proteomic, and metabolomic technologies to the interrogation of static samples in model systems of human disease. The integration of the results of these technologies under the banner of systems biology holds much promise. In this forward-looking essay, we posit that to fully understand human biology, such measurements not only need to be integrated, but conducted in humans in real time through the merging of molecular biology and imaging technologies.